(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
For the fabrication of customized silicone rubber-based implants, e.g. cochlear implants or electrocortical grid arrays with high resolution, 3D printing is not only a great option but also a challenging one. 3D printing of medical approved silicone will enable a highly personalized medicine. The introduction of electronics, conductors and electrodes which are needed for creating active implants includes some challenges. These are the printing of the high viscous non-Newtonian medical approved silicone rubber. It is also required to develop high speed curing systems, which vulcanize the silicone rubber systems to prevent extensive spreading of the viscous silicone materials during vulcanization.